Influence of Pharmacy Characteristics and Customer Quality of Life on Satisfaction of Community Pharmacy Customers - Ali Azeez Al-Jumaili; Inaam Ahmed Ameen; Doaa Asaad Alzubaidy (University of Minnesota Libraries Publishing, 2020)
Objectives: The study objectives were to evaluate customer satisfaction with community pharmacy services and measure the relationships between customer satisfaction and pharmacy/pharmacist characteristics and customer quality of life. Methods: This was a cross-sectional survey of a convenience sample of customers at 20 community pharmacies in 10 different geographical areas in Baghdad city between May and September 2018. We used the satisfaction items which were developed by Paterson and colleagues in 2013. The survey also assessed customer quality of life (QoL) with 12 QoL items. Results: The study recruited 400 pharmacy customers. Overall, customers reported good satisfaction with community pharmacy services. The most three satisfying aspects were the professional appearance of the pharmacy, the professionalism of pharmacy staff and explanations of possible adverse medication effects. Three customer characteristics were associated with high satisfaction rates including male gender, buying medications without a prescription, and seeking services for themselves. Three pharmacy characteristics increased the customer satisfaction rate including the availability of female pharmacists, having more than one pharmacist, and whether the pharmacy is open full time. For quality of life, patients who had a limitation in their activities and those who accomplished less than they would like were less satisfied with pharmacy services.   Conclusions:  To improve pharmacy services, pharmacists need to enhance their professional appearance, allocate more time for patient counselling, help patients to manage their medications and extend their working hours to meet customer needs.   Article Type: Original Research